Urgensi Pendekatan Hermeneutik Dalam Memahami Al-Qur’an - Nikmah, Alfi (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
The way to understand the Qur'an and understand the meaning or content in the Qur'an is to understand the editorial of the Qur'an directly. In this way, we will be able to feel (tadzawwuq) the pulses of the Qur'an's description that are so beautiful and charming. However, because not all Muslims are able to understand the editorial of the Qur'an directly it needs to be translated into other languages. This understanding of the Qur'an uses the study of the hermeneutic method which is from time to time has experienced significant developments in qualitative research, including being a stream of philosophical science and applied in the humanities (social humanitarian) sciences, namely "interpretive flow".  The purpose of this study is that translators are required to know the material being translated well. If the translated verse is related to legal matters, then the intricacies of the legal issues must be known. If it is not, some errors can occur in the translation. To get closer to the truth, a translator of the Qur'an needs to see and examine the interpretive books. If there are several understandings of one verse, then he has a literal translation meaning, namely a translator is faced with a narrow choice, therefore he only takes one meaning from the many meanings available. If there are several understandings of one verse, then it has a literal translation meaning, that is, a translator is faced with a narrow choice, therefore he only takes one meaning from the many existing meanings. So the findings of this study are the recognition that each language has its own specifications which cannot be found in other languages. Therefore, it is not possible for one translation to match one hundred percent of what the first speaker wants. This is the object of many to the literal translation of the Qur'an.